Analysis of foreign direct investments: regional aspect - I. V. Shevchenko; M. K. Tretyakova (Вестник университета)
The article analyses the dynamics of foreign direct investments in Russia and the world. Developed countries act as net lenders. Developing countries are borrowers in the investment capital market. The paper reveals the trend of reducing the balance of foreign direct investments in Russia, especially after the introduction of sanctions in 2014. Assessment of the structure of foreign direct investments by Federal Districts shows the presence of territorial imbalances in the distribution of foreign capital. The largest volume of foreign direct investments is in the Central Federal District. In the Krasnodar Territory, the balance of foreign direct investments is positive, but has an uneven dynamics. The authors make conclusions about the need to stimulate the inflow of foreign direct investments both at the level of Russia and in the Krasnodar Territory.